Adjacency and Incidence Matrix of a Soft Graph - Thenge, J. D.; Reddy, B. Surendranath; Jain, Rupali (Communications in Mathematics and Applications, 2020)
In the present paper we define the notion of adjacency matrix and incidence matrix of a soft graph and derive some results regarding these matrices. We show that some of the classical results of graph theory does not hold for soft graphs.
Keywords: Soft set; Soft graph; Adjacency matrix; Incidence matrix